Evaluation of the Approaches and Methods of Teaching a Second Language from a Structural Perspective. - Dana Tahsin Mohammed; Abdullah Hussein Rasool. (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Evaluating the approaches and methods of teaching the second language from a structural perspective is the title of the present research. The aim of this research is to explore the best and most appropriate approach and method for teaching the second language from a structural perspective. Two main topics: The first topic: includes the following titles: approaches and methods of teaching the second language from a structural perspective, the oral approach, the aural-oral approach, the direct method, total physical response method, and the silent way. As for the second topic, it deals with the title: Evaluation of the Approaches and Methods of Teaching the Second Language from a Structural Perspective. At the conclusion of the research, the following results were reached: The best and most appropriate approach and method for teaching the second language from a structural perspective is the aural-oral doctrine, and that two methods (total physical response and the silent) are only suitable for the first level of teaching the second language.